Sustained Abdominal Aorta Compression Elevates Coronary Perfusion Pressure after Asphyxia-Induced Cardiac Arrest in a Rabbit Model. Issue 1 (January 2013) - Wang, LX; Liu, YH; Li, XM; Shi, HZ; Ji, ZX; Guo, XD; Sun, K; Ma, LZ; Guo, CC
Objective: To investigate whether sustained abdominal aorta compression (SAAC) can improve coronary perfusion pressure (CPP) during cardiopulmonary resuscitation (CPR) and improve resuscitation outcomes without causing liver laceration. Design and Setting: Animal study. Methods: Cardiac arrest was induced by asphyxia in 28 New Zealand rabbits and maintained for 2 minutes before resuscitation. Animals were resuscitated using either standard CPR (STD-CPR group) or standard CPR and SAAC (SAAC-CPR group). Restoration of spontaneous circulation (ROSC), restoration of spontaneous breathing (ROSB) and cerebral performance category score were determined. CPP, mean arterial pressure (MAP) and ROSC were compared in the two groups. Results: MAP and CPP in the SAAC-CPR group were significantly higher than in the STD-CPR group. However, MAP and blood gas results showed no significant difference between the two groups during ROSC. ROSC was achieved in seven of fourteen animals in the STD-CPR group and in eleven of fourteen animals in the SAAC-CPR group. Five animals in the STD-CPR group and nine in the SAAC-CPR group survived 24 hours after ROSC. No liver injury occurred in the two groups. Conclusions: SAAC-CPR produces an increased CPP and MAP than traditional CPR and it does not lead to liver laceration/injury.